Extraction of safflower seed oil by supercritical CO2 - Han, H.; Cheng, L.; Zhang, R.; Bi, J.
Safflower seed oil extraction with supercritical CO2 at series operational parameters of pressure, temperature, flow rate and particle size was investigated in a bench scale apparatus. The results show that the extraction yields plotted as a function of time are significantly affected by the extraction pressure, flow rate and particle size, but extraction yields plotted versus CO2 used are scarcely affected by flow rate. Extraction temperature has a slight effect on the extraction curves. In order to describe the extraction process, the Sovova's extended Lack's Model (SLM)was used and the experimental data were well fitted by it. The extraction was scaled up to pilot plant and the computed values of SLM are in good agreement with the pilot plant data. Additionally, the quality of safflower seed oil obtained by supercritical CO2 extraction is superior to that of oil obtained by traditional methods. It is noted that a new method of changing flow rate was proposed to improve the process efficiency and proved to be valuable by experiment.
Keywords: SUPERCRITICAL CO2 EXTRACTION; SAFFLOWER SEED OIL; MATHEMATICAL MODEL; SCALE UP